Pseudoanglizismen im dänischen - Szubert, Andrzej (Folia Scandinavica Posnaniensia, 2007)
In the following paper the author analyses English pseudoloans in Danish. The problem has not been given received much interest and neither has it been researched thoroughly so far. The paper is an attempt to define pseudoloans and to describe Danish words that are formed out of English morphemes.